PENGARUH TINGKAT KEADILAN PROSEDURAL TERHADAP KEPATUHAN WAJIB PAJAK: VARIABEL KEPERCAYAAN TERHADAP OTORITAS PAJAK DAN NORMA PERSONAL SEBAGAI VARIABEL MODERATOR DAN MEDIATOR (Studi Empiris Pada Wajib Pajak Yang Melakukan Kegiatan Usaha Di Kota Semarang) - Mohamad Danand Giswa; Indira Januarti (Diponegoro Journal of Accounting, 2015)
This study aims to analyze the effect of procedural fairness on taxpater’s compliance andthe role of trust in tax authorities and personal norms as moderator and mediator variables. Fairness Heuristic Theory explains trust in the tax authorities can strengthen the influence of procedural fairness on tax compliance. While based on the norm activation theory developed by Scwartz (1973; 1977), presented mediation model, which is personal norms role as mediator variables on the influence of procedural fairness to the taxpayer’s compliance. This study uses a quantitative method where the data obtained from the questionnaire with convenience sampling technique. The respondents in this research is the taxpayer who carries on business in the city of Semarang, both of which are businesses individual taxpayers and corporate taxpayers. Data was analyzed using regression analysis, moderated regression analysis, and path analysis with SPSS 20:00 for windows. Based on the research that has been done, procedural fairness have a direct negative effect on tax compliance, but have an indirect positive effect through the mediator variable personal norms, in addition the effect of procedural fairness on tax compliance can be strengthened by a moderator variable of trust in tax authorities.